Strategi Manajemen Perubahan Perusahaan di Era Digital - Pupung purnamasari; Agung Bagus Presetyo; Ade Syahrozi; Padly Nahampun (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Change management is an approach taken by individuals or organizations to move from previous conditions to a better future. In the midst of rapid advances in digital technology, business organizations are required to be able to adapt in order to remain competitive. Digital transformation brings fundamental changes in various operational aspects, so companies need to make adjustments, not only in terms of technology, but also in terms of work culture, organizational structure, and the mindset of their human resources. This research aims to discuss concepts and practical approaches in managing business organizational change in the digital era, so that the digital transformation process can be carried out with careful planning and appropriate strategies. This research was conducted using the literature study method, referring to various sources such as e-books and previous journals. The results showed that changes in organizations are usually driven by common goals that are adjusted to the increasingly rapid development of technology. Change is inevitable and must be managed in a structured way to produce a positive impact. Through proper change management, organizations can increase effectiveness and innovation so that they can survive and thrive in global competition. Digital transformation that is carried out thoroughly and sustainably will create organizational readiness to face the changing dynamics in this digital era.